IMPLICATIONS OF MADRASA GUIDANCE AND COUNSELING SERVICES TO PREVENT CHILD MARRIAGE IN CENTRAL LOMBOK REGENCY - Lalu Abdurrachman Wahid (Al-Tazkiah Jurnal Bimbingan dan Konseling Islam, 2024)
This study aims to detail the implementation of counseling services in Madrasas, examine the obstacles hindering these services, and propose measures to overcome these challenges to prevent child marriages in Central Lombok Regency. Adopting a qualitative research design with a descriptive approach, the research was carried out at MAN 1 Lombok Tengah and MTsN 1 Lombok Tengah. Primary data were obtained through observations and interviews with students, counseling teachers, and Madrasa leaders, while secondary data were sourced from documentation. The data analysis involved reduction, presentation, verification, and conclusion drawing. The results reveal that counseling services in Madrasas, which include essential services, specialized and individual planning services, responsive services, and systemic support, play a significant role in preventing child marriages. Internal barriers to effective counseling include the insufficient competency and experience of counseling teachers, health and age-related issues, lack of motivation and work discipline, and suboptimal planning and execution of counseling services. External barriers include inadequate facilities and infrastructure, poor coordination between Madrasa leadership and local authorities and related institutions, a shortage of counseling teachers, economic instability, and low awareness and participation from students and parents. To address these challenges, counseling teachers and Madrasa leaders have undertaken various initiatives. Successfully preventing and reducing child marriages requires the concerted effort of all school personnel and external stakeholders, including parents and relevant institutions.